Obesity and Overweight Are Associated with Minimal Extrathyroidal Extension, Multifocality and Bilaterality of Papillary Thyroid Cancer - Krzysztof Kaliszewski (Journal of Clinical Medicine, 2021)
Epidemiological studies have shown a strong association between high body mass index (BMI) and papillary thyroid cancer (PTC). We assessed the clinical and histopathological features of PTC in patients with a higher BMI and compared them to analogous parameters in PTC patients with a normal BMI. We retrospectively analyzed 5021 medical records of patients admitted and surgically treated for thyroid tumors in one center between 2008 and 2018. Finally, we extracted data from 523 adult patients with PTC and stratified patients into two groups according to BMI: Group 1 with BMI < 25 kg/m2 and Group 2 with BMI ≥ 25 kg/m2. Data stratification was performed to estimate the association of overweight and obesity with clinical and histopathological features of PTC in both univariable and multivariable binary logistic regression analyses. Overall, compared to patients with a normal BMI, overweight and obese patients had a greater risk of minimal extrathyroidal extension (minimal ETE), multifocality and bilaterality of PTC (p < 0.001 for all). Analysis did not show that BMI was significantly associated with the more advanced tumor-node-metastasis (TNM) stage (p = 0.894). Obesity and overweight were significantly associated with higher aggressiveness of PTC. When considering various management options for PTC patients, these findings regarding overweight and obesity should be taken into consideration during the decision-making process.